Manfaat Penyuluhan Dengan Media Leaflet Terhadap Pengetahuan Remaja Putri Tentang Anemia - Ni Nyoman Manik Sugiarti; I Komang Lindayani; Ni Made Dwi Mahayati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2020)
Anemia is one of the health problems that occur in adolescents, one of the cause factor of anemia is nutritional status. The purpose of this study is to determine the benefits of health education with leaflet media on the level of knowledge about anemia in adolescent girls in SMA N 1 Semarapura. This study uses a pre-experimental research design with the design of one group pretest-posttest. The study population was the entire X-MIPA grade students who meets the inclusion and exclusion criteria. Sampling using proportional cluster random sampling to the number of 37 samples. Data were collected primary data through questionnaires. Results from this study that the median value of knowledge before the health education is given is 65, while the median value after health education is given is 95. Wilcoxon test results showed that there were significant differences in student knowledge before and after the given extension (p value (0.000) α (0.05)). Conclusions from this research is that there are benefits of health education with leaflet media against the adolescents knowledge about anemia.